Il problema energetico: fondamentale, ma non è l’unico - Balzani, Vincenzo; Venturi, Margherita (Chimica nella Scuola, 2023)
We are facing a complex crisis which is both environmental and social. Sadly, not many seem to be aware of the challenge we face. The first thing to do is to inform and educate people to build a solid cultural foundation and to implement a courageous cultural revolution. We need to change our current lifestyle to reduce waste and pollution and, most important, to stop climate change. We also need to reduce the growing inequalities between nations and within each nation. To achieve these objectives, we must create a new economic model based on ethical foundations, aimed at promoting ecological as well as social sustainability. Strategies for a solution demand an integrated approach to protecting nature and combating poverty by the implementation of three transitions: from fossil fuels to renewable energies, from a linear to a circular economy, and from consumerism to sobriety. We must protect our planet because it must also serve the next generations. There is so much to be done to improve this world. Many decisions must be made at a political level, but each of us is required to play our part